Gateway District: The Opportunities of City Gate as a Growth Centre Reinforcement. - Dwi Lindarto; D.D Harisdani (Talenta Publisher, 2019)
Inauguration Kuala Namu Airport in 2012 has established access to area of Medan, Binjai, Deli Serdang and Karo (Mebidangro) region as a leading tourist destination. As the central hub to the area declared Mebidangro, Medan city railway station in the center of Merdeka Square as a main gate. The facts show that the concept of the gates are inadequate in physical appearance as well as activities that memorable as the charming gateway. In simple terms refers to a landmark gate marker. City revitalization in addition to using a model of revitalization can be done with a model revealing the wisdom of local activities. In the era of visual communication and local activities as opportunities for the development of a place, the potential Merdeka Square neighborhood activities become eligible as an aspect of quality amplifier forming place (reinforcement place making). With the method of observation and analysis of spatial solid-void it is obtained that the Merdeka Square is a model of district gateway rather than a landmark gateway by appearing the activities of local commercial, local culture, heritage adventure, social interaction as a trigger activity. These findings are useful for policy makers to look at the Merdeka Square as forming productivity growth Medan city center as well as reinforcing the identity of Medan city.